PASAR KOPI INDIA DAN PENINGKATAN EKSPOR KOPI INDONESIA TAHUN 2018-2022 - ', Maharani; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Coffee is one of Indonesia's leading plantation commodities with high economic value and plays a significant role in the international trade sector. India, as one of the export destination countries, has shown a significant increase in demand for Indonesian coffee. In 2018, Indonesia’s coffee exports to India reached only 2,237 tons, but experienced a sharp increase to 43,651 tons by 2022. This reflects a competitive trade dynamic and highlights the importance of analyzing Indonesia's export competitiveness. This study employs a qualitative method using secondary data obtained from trade reports, academic journals, as well as publications from the government and the Central Bureau of Statistics (BPS). The research adopts a liberalism perspective and the theory of comparative advantage. The increase in Indonesian coffee exports to India is influenced by several factors, including rising Indian demand for premium and specialty coffee, supportive tariff and non-tariff policies, Indonesian coffee competitiveness, coffee production, coffee marketing strategy and trade agreements between the two countries that facilitate market access. Keywords: Coffee Export, Indonesia–India, International Trade